AI systems at the test of Revelation: From the Promise of Augmented Intelligence to the Perils of Human Dehumanization - Belabes, Abderrazak (Universitas Muhammadiyah Surakarta, 2026)
This research offers a reflection on AI systems in light of the Quranic verse, (He Is The One Who Created for You Allah that is on the Earth) (Qur'ān, 2: 29). It challenges the traditional view that reduces technology to a mere neutral instrument, revealing instead that it is a profoundly existential, ontological, and ethical human endeavor, demanding responsibility, discernment, and regulation. The study emphasizes that mastering AI systems does not grant humanity absolute sovereignty, but rather places it in the position of mustakhlaf (steward of the earth) and amīn (trustworthy), charged with preserving the balance between creatures and guaranteeing their rights. It warns against the temptation to make AI an end in itself, which could alienate humanity and sever its transcendent connection with the world order through a vertical causality. From this perspective, AI presents itself as a true mirror of human commitment, revealing the depth of our responsibility towards the designs of creation and the realization of the common good, liberated from all pursuit of material domination and any descent into nihilism.